Analisis Faktor-Faktor Yang Mempengaruhi Suksesi Keberhasilan Bisnis Keluarga - Della Nur Shayidah; Rusnandari Retno Cahyani (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2024)
Family businesses are controlled by family members through blood ties or marriage and reflect characteristics such as family commitment, learning environment, reliability, spiritual strength, and dual leadership. Sustainability in family businesses is considered a core goal of business, but challenges arise from internal conflicts, generational differences, and adaptation to non-traditional methods. Heritage values and family traditions play an important role in in decision making. Factors such as inheritance for generations, risk management, and organizational culture also affect family business identity and performance. A literature review discusses preparation, family relationships, and planning as important factors in family business succession.